‘We are… we are everything’: the politics of recognition and misrecognition at immigration museums - Smith, Laurajane (Museum and Society, 2017)
Qualitative interviews were undertaken with visitors at five museums that display the histories and experiences of immigration in the United States and Australia. This paper outlines the range of embodied performative practices of meaning making that visitors undertook during their visits and the meanings and political values that they created or reaffirmed in doing so. The key performance at these museums were the affirmation and reinforcement of familial, ethnic and national identities in which individuals explored the tensions between migrant identity and the nationalizing narratives of the resident nation. The performance of reinforcement could also be used to justify both politically progressive and conservative narratives of inclusion and exclusion. Building on performances of reinforcement some visitors also engaged in acts of justification, recognition and misrecognition. In illustrating and mapping out the range of banal and complex ways these museums were used by visitors, the paper argues that museums may be more usefully understood as arenas of justification rather than resources for public education.